Lipid–Polymer Hybrid Nanoparticles for mRNA Delivery to Dendritic Cells: Impact of Lipid Composition on Performance in Different Media - Lena Kliesch; Simon Delandre; Aljoscha Gabelmann; Marcus Koch; Kai Schulze; Carlos A. Guzmán; Brigitta Loretz; Claus-Michael Lehr (Pharmaceutics, 2022)
To combine the excellent transfection properties of lipids with the high stability of polymeric nanoparticles, we designed a hybrid system with a polymeric core surrounded by a shell of different lipids. The aim is to use this technology for skin vaccination purposes where the transfection of dendritic cells is crucial. Based on a carrier made of PLGA and the positively charged lipid DOTMA, we prepared a panel of nanocarriers with increasing amounts of the zwitterionic phospholipid DOPE in the lipid layer to improve their cell tolerability. We selected a nomenclature accordingly with numbers in brackets to represent the used mol% of DOPE and DOTMA in the lipid layer, respectively. We loaded mRNA onto the surface and assessed the mRNA binding efficacy and the degree of protection against RNases. We investigated the influence of the lipid composition on the toxicity, uptake and transfection in the dendritic cell line DC 2.4 challenging the formulations with different medium supplements like fetal calf serum (FCS) and salts. After selecting the most promising candidate, we performed an immune stimulation assay with primary mouse derived dendritic cells. The experiments showed that all tested lipid–polymer nanoparticles (LPNs) have comparable hydrodynamic parameters with sizes between 200 and 250 nm and are able to bind mRNA electrostatically due to their positive zetapotential (20–40 mV for most formulations). The more of DOPE we add, the more free mRNA we find and the better the cellular uptake reaching approx. 100% for LPN(60/40)–LPN(90/10). This applies for all tested formulations leading to LPN(70/30) with the best performance, in terms of 67% of live cells with protein expression. In that case, the supplements of the medium did not influence the transfection efficacy (56% vs. 67% (suppl. medium) for live cells and 63% vs. 71% in total population). We finally confirmed this finding using mouse derived primary immune cells. We can conclude that a certain amount of DOTMA in the lipid coating of the polymer core is essential for complexation of the mRNA, but the zwitterionic phospholipid DOPE is also important for the particles’ performance in supplemented media.